2020
DOI: 10.1111/ejh.13471
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of apixaban and rivaroxaban for acute venous thromboembolism therapy in patients with extremes in bodyweight

Abstract: Objectives To investigate the association of extremes in bodyweight (EBW) and outcomes in patients with acute venous thromboembolism (VTE). Recurrent VTE, major bleeding, and clinically relevant non‐major bleeding were compared between patients with bodyweight <60 kg, 60‐120 kg, and >120 kg. Methods Consecutive patients enrolled in the Mayo Clinic VTE Registry (03/28/2013‐8/31/2019) with acute VTE were followed prospectively. Patient status was assessed in person, by mailing a written questionnaire, or by a sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Another study in 366 patients with a BMI ≥ 40 kg/m 2 prescribed an anticoagulant for venous thromboembolism (apixaban, n = 47; rivaroxaban, n = 152; warfarin, n = 167) found the incidences of recurrent VTE and major bleeding to be similar between each NOAC and warfarin [ 21 ]. An analysis of the Mayo Clinic VTE Registry consisting of 2577 patients with VTE receiving anticoagulant treatment (apixaban, n = 772; rivaroxaban, n = 502) found similar rates of recurrent VTE and major bleeding between apixaban-treated and rivaroxaban-treated patients across body weight groups (< 60, 60 to 120, and > 120 kg) [ 22 ]. Observational data comparing rivaroxaban with warfarin are available from a propensity score-matched analysis using pooled data from two US claims databases.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in 366 patients with a BMI ≥ 40 kg/m 2 prescribed an anticoagulant for venous thromboembolism (apixaban, n = 47; rivaroxaban, n = 152; warfarin, n = 167) found the incidences of recurrent VTE and major bleeding to be similar between each NOAC and warfarin [ 21 ]. An analysis of the Mayo Clinic VTE Registry consisting of 2577 patients with VTE receiving anticoagulant treatment (apixaban, n = 772; rivaroxaban, n = 502) found similar rates of recurrent VTE and major bleeding between apixaban-treated and rivaroxaban-treated patients across body weight groups (< 60, 60 to 120, and > 120 kg) [ 22 ]. Observational data comparing rivaroxaban with warfarin are available from a propensity score-matched analysis using pooled data from two US claims databases.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found recurrent VTE and major bleeding rates that were reduced by more than one-half in obese patients receiving a DOAC compared with a low-molecularweight heparin (LMWH) or warfarin (►Table 6). 84 Again, these results may be clinically meaningful, but only 8.5% of the patients in this study weighed greater than 120 kg. One study attempted to compare rivaroxaban to apixaban and found a rate of recurrent VTE of 6.4% in those receiving rivaroxaban and 0% in patient receiving apixaban (p ¼ 0.49).…”
Section: Data From Observational Studiesmentioning
confidence: 58%
“…In a prospective observational study, patients weighing less than 60 kg receiving apixaban or rivaroxaban for the treatment of VTE (n ¼ 90) had one-half the rate of recurrent VTE at 3 months compared with patients receiving a DOAC in the reference weight group (n ¼ 1,076; 1.5 vs. 3.2%; p ¼ 0.43), but a doubling in the rate of major bleeding (6.1 vs. 2.7%; p ¼ 0.15). 84 These same trends were also demonstrated with the use of a LMWH and VKA. Use of apixaban or rivaroxaban in these patients with low body weight had a nonsignificant 70% reduction in recurrent VTE (1.5 vs. 5.3%; p ¼ 0.25), and a nonsignificant 44% reduction in major bleeding (6.1 vs. 10.9%; p ¼ 0.32) compared with the use of a LMWH and VKA (n ¼ 71).…”
Section: Underweight Patientsmentioning
confidence: 61%
See 2 more Smart Citations